Respuesta :

Answer:

a.   Slope of f(x) is greater than g(x)

b.   y-intercept of f(x) is less than the y-intercept of g

Step-by-step explanation:

                                               Function f(x)

Given the function f(x)

x            f(x)

-3          -0.5

-2           0

-1            0.5

0             1

Finding the slope between any two points

[tex]\mathrm{Slope}=\frac{y_2-y_1}{x_2-x_1}[/tex]

[tex]\left(x_1,\:y_1\right)=\left(-3,\:-0.5\right),\:\left(x_2,\:y_2\right)=\left(-2,\:0\right)[/tex]

[tex]m=\frac{0-\left(-0.5\right)}{-2-\left(-3\right)}[/tex]

[tex]m=0.5[/tex]

Thus,

The slope of f(x) = 0.5

We know that the value of the y-intercept can be determined by setting x = 0, and determining the corresponding value of y.

From the given point (0, 1), we can easily observe that at x = 0, the value of y = 1.

Thus, the y-intercept of f(x) = 1

                                             Function g(x)

Taking two points from the given graph of g(x)

  • (1, 0)
  • (0, 2)

Finding the slope between (1, 0) and (0, 2)

[tex]\mathrm{Slope}=\frac{y_2-y_1}{x_2-x_1}[/tex]

[tex]\left(x_1,\:y_1\right)=\left(1,\:0\right),\:\left(x_2,\:y_2\right)=\left(0,\:2\right)[/tex]

[tex]m=\frac{2-0}{0-1}[/tex]

Refine

[tex]m=-2[/tex]

Thus,

The slope of g(x)  = -2

We know that the value of the y-intercept can be determined by setting x = 0, and determining the corresponding value of y.

From the given point (0, 2), we can easily observe that at x = 0, the value of y = 2.

Thus, the y-intercept of g(x) = 2

Conclusion:

FOR function f(x)

The slope of f(x) = 0.5

The y-intercept of f(x) = 1

FOR function gx)

The slope of g(x) = -2

The y-intercept of g(x) = 2

Thus:

a.   Slope of f(x) is greater than g(x)

b.   y-intercept of f(x) is less than the y-intercept of g

ACCESS MORE